PENGARUH MOTIVASI, PENGHARGAAN DAN HUKUMAN TERHADAP KINERJA PADA KARYAWAN PT SUMBER BERKAH MANDIRI BANDAR LAMPUNG - Majid, Sugiarto; Wuryanti, Lestari; Lukman, Iing (Universitas Malahayati, 2021)
This study aims to test and prove the influence of motivation, reward and punishment on the performance of employees of PT Sumber Berkah Mandiri Bandar Lampung. The population in this study were 30 employees of PT Sumber Berkah Mandiri Bandar Lampung from the 2019-2020 period.The variables used are 3 variables. The analysis tool used is multiple regression analysis. The results of the analysis show that: a) the motivation variable has no effect on performance. b) the reward variable has no effect on performance. c) Punishment variables have an effect on performance.Keywords: Motivation, Rewards and Punishment for EmployeePerformance